Legal Protection for Problem Debtor Related to the Use of the Artificial Intelligence System in Peer to Peer Lending - Yusuf Arif Utomo (Universitas Airlangga, 2020)
In the era of digital economic development, the community continues to innovate in terms of providing lending and borrowing services. One form of development of Financial Technology (fintech) is the distribution of funds through the Peer to Peer (P2P) Lending system. Where this system has more or less the same role as banks, namely as an organizer; from parties who have funds (investors) to those who need funds (debtors) whose methods are carried out online. The distribution of funds through the P2P Lending system has developed rapidly in Indonesia. In carrying out its business, the loan and loan service provider uses an electronic system that is a series of electronic devices and procedures that function to disseminate information in the field of financial services. The electronic system can also be referred to as Artificial Intelligence (AI). By using AI, loan and loan service providers can find out all the debtor's personal data, where in the end the debtor becomes disadvantaged because his personal rights are violated. On the other hand there are no legal provisions in Indonesia that can protect debtors in this regard. So that in this study later will discuss about the extent of legal arrangements related to the protection of debtors in the P2P Lending system using AI. This research uses the statute approach method; namely the approach through legislation and conceptual approach, namely the legal approach through the concepts and opinions of legal experts.